2014
DOI: 10.1242/jeb.096883
|View full text |Cite
|
Sign up to set email alerts
|

Prior experience with conspecific signals enhances auditory midbrain responsiveness to conspecific vocalizations

Abstract: There is a long history in neuroethology of investigating how communication signals influence the brain and behavior. It has become increasingly clear that brain areas associated with sensory processing are plastic in adults and that this plasticity is related to reproductive condition. However, the role of communication signal reception in adult auditory plasticity has received relatively little attention. Here, we investigated whether the reception of communication signals (a frog chorus) could enhance the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Our recent work suggests that experience with social stimuli can also induce plasticity in both the auditory midbrain (Gall and Wilczynski, 2014) and in the auditory periphery by changing response strength to conspecific call frequencies (Gall and Wilczynski, 2015). The current results show that socially induced auditory plasticity extends to facilitating release from forward masking, which may be particularly important in real-world complex acoustic conditions.…”
Section: Forward Masking and Socially Induced Plasticitymentioning
confidence: 49%
“…Our recent work suggests that experience with social stimuli can also induce plasticity in both the auditory midbrain (Gall and Wilczynski, 2014) and in the auditory periphery by changing response strength to conspecific call frequencies (Gall and Wilczynski, 2015). The current results show that socially induced auditory plasticity extends to facilitating release from forward masking, which may be particularly important in real-world complex acoustic conditions.…”
Section: Forward Masking and Socially Induced Plasticitymentioning
confidence: 49%
“…Exposure to a particular song type for one week enhanced telencephalic responses to novel exemplars of that type in European starlings (Sturnus vulgaris) [12,13]. Similarly, we recently found that green treefrogs (Hyla cinerea) that heard a simulated chorus nightly for 10 days had significantly increased immediate early gene responses to novel conspecific advertisement calls in the auditory midbrain [14].…”
Section: Introductionmentioning
confidence: 59%
“…This suggests that the differences in response to conspecific and heterospecific songs recorded in MLd are not simply a result of repeated exposure to a particular auditory stimulus. Repeated exposure has been shown to change neural responses in the auditory cortex of rats (Bao et al, 2013), ferrets (Schnupp et al, 2006), and gerbils (Caras & Sanes, 2017), and in the auditory midbrain of mice (Cruces-Solís et al, 2018) and frogs (Gall & Wilczynski, 2014). Instead, the persistence of the differences observed in the MLd of both groups of birds, suggest that these changes may be influenced by the critical period of learning associated with song learning.…”
Section: Resultsmentioning
confidence: 99%